Perlindungan Rahasia Dagang dalam Kerangka Haki: Studi Komparatif Indonesia dan Malaysia - Ismarini Della Purnama; Muhammad Arya Azra; Renofadli Rizkisyah; Atik Winarti (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the protection of trade secrets in the framework of Intellectual Property Rights (IPR) by conducting a comparative study between Indonesia and Malaysia. Trade secrets are a form of intellectual property that has significant economic value for business actors but often receives inadequate attention compared to other forms of IPR. This research focuses on two main problems: first, the comparison of the legal framework for the protection of trade secrets in Indonesia and Malaysia in the context of Intellectual Property Rights; and second, the role of IPR-related institutions in both countries in providing protection for trade secrets. The research method used is normative legal research with a comparative approach and a statute approach. The data used are in the form of primary legal materials in the form of laws and regulations related to IPR in Indonesia and Malaysia, as well as secondary legal materials in the form of literature and scientific journals. The results of the study show that there are significant differences in the legal framework for the protection of trade secrets between Indonesia, which adopts a civil law system with special codification through Law No. 30 of 2000, and Malaysia, which applies a common law approach with a combination of court precedents and statutory law. In addition, there are differences in the roles and functions of IPR-related institutions in the two countries in providing protection for trade secrets, especially in terms of registration, law enforcement, and dispute resolution. The study concludes that despite differences in approaches, both Indonesia and Malaysia recognize the importance of trade secret protection within the framework of IPR, with Malaysia tending to have a more comprehensive protection system based on common law practices. Based on the findings of the study, it is recommended that Indonesia can adopt some positive aspects of Malaysia's trade secrets protection system, especially in terms of harmonizing the role of relevant institutions and strengthening law enforcement mechanisms.